A new pharmacodynamic approach to study antibiotic combinations against enterococci in vivo: Application to ampicillin plus ceftriaxone (2020)
ABSTRACT: The combination of ampicillin (AMP) and ceftriaxone (CRO) is considered synergistic against Enterococcus faecalis based on in vitro tests and the rabbit endocarditis model, however, in vitro assays are limited by the use of fixed antibiotic concentrations and the rabbit model by poor bacterial growth, high variability, and the use of point dose-effect estimations, that may lead to inaccurate assessment of antibiotic combinations and hinder optimal translation. Here, we tested AMP+CRO against two strains of E. faecalis and one of E. faecium in an optimized mouse thigh infection model that yields high bacterial growth and allows to define the complete dose-response relationship. By fitting Hill’s sigmoid model and estimating the parameters maximal effect (Emax) and effective dose 50 (ED50), the following interactions were defined: synergism (Emax increase ≥2 log10 CFU/g), antagonism (Emax reduction ≥1 log10 CFU/g) and potentiation (ED50 reduction ≥50% without changes in Emax). AMP monotherapy was effective against the three strains, yielding valid dose-response curves in terms of dose and the index fT>MIC. CRO monotherapy showed no effect. The combination AMP+CRO against E. faecalis led to potentiation (59–81% ED50 reduction) and not synergism (no changes in Emax). Against E. faecium, the combination was indifferent. The optimized mouse infection model allowed to obtain the complete dose-response curve of AMP+CRO and to define its interaction based on pharmacodynamic parameter changes. Integrating these results with the pharmacokinetics will allow to derive the PK/PD index bound to the activity of the combination, essential for proper translation to the clinic.